Survival after adding capecitabine and trastuzumab to neoadjuvant anthracycline-taxane-based chemotherapy for primary breast cancer (GBG 40–GeparQuattro) - Von Minckwitz, G.; Rezai, M.; Fasching, Peter; Huober, J.; Tesch, H.; Bauerfeind, I.; Hilfrich, J.; Eidtmann, H.; Gerber, B.; Hanusch, C.; Blohmer, J. U.; Costa, S. D.; et al. (Annals of Oncology, 2014)
The GeparQuattro study showed that adding capecitabine or prolonging the duration of anthracycline-taxane-based neoadjuvant chemotherapy from 24 to 36 weeks did not increase pathological complete response (pCR) rates. Trastuzumab-treated patients with HER2-positive disease showed a higher pCR rate than patients with HER2-negative disease treated with chemotherapy alone. We here present disease-free (DFS) and overall survival (OS) analyses.Patients (n = 1495) with cT >= 3 tumors, or negative hormone-receptor status, or positive hormone-receptor and clinically node-positive disease received four times epirubicin/cyclophosphamide and were thereafter randomly assigned to four times docetaxel (Taxotere), or four times docetaxel/capecitabine over 24 weeks, or four times docetaxel followed by capecitabine over 36 weeks. Patients with HER2-positive tumors received 1 year of trastuzumab, starting with the first chemotherapy cycle. Follow-up was available for a median of 5.4 years.Outcome was not improved for patients receiving capecitabine (HR 0.92; P = 0.463 for DFS and HR 93; P = 0.618 for OS) as well as for patients receiving 36 weeks of chemotherapy (HR 0.97; P = 0.818 for DFS and HR 0.97; P = 0.825 for OS). Trastuzumab-treated patients with HER2-positive disease showed similar DFS (P = 0.305) but a significantly better adjusted OS (P = 0.040) when compared with patients with HER2-negative disease treated with chemotherapy alone. Recorded long-term cardiac toxicity was low.Long-term results, similar to the results of pCR, do not support the use of capecitabine in the neoadjuvant setting in addition to an anthracycline-taxane-based chemotherapy. However, the results support previous data showing a benefit of trastuzumab as predicted by higher pCR rates.
EVALuna2:17517